Analysis Of Awareness, Services, Counseling, And Tax Sanctions On Compliance With Individual Business Persons - Apriliyanto, Muhammad Primbang (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to analyze taxpayer awareness, tax services, tax counselling and tax sanction on individual entrepreneur taxpayer compliance at the Regional Office of DJP East Java II. The population in this study are all individual business tax payers who are registered at the Tax Service- Office (KPP) in the East Java II Regional Office at DJP. With a research sample of 3 businessmen OP Taxpayers with descriptive qualitative methodological technique. Data collection was carried out through interview, observation and documentation. The result of this study prove that partially taxpayer awareness, tax services, tax counselling and tax sanctions have a positive and significant effect on individual entre preneur taxpayer compliance at KPP KPP in the Regional Office of DJP East Java II. This means that the increasing awareness of taxpayers, good tax services, counselling of taxpayers, and tax sanction, the taxpayer compliance will be better (increased).